Short- and medium-term impact of manual tillage and no-tillage withmulching on banana roots and yields in banana-bean intercroppingsystems in the East African Highlands - Muliele, M.T.; Bielders, Charles L.; Asten, Piet J.A. van (Elsevier, 2015)
tBanana-bean intercropping systems are common in the bimodal rainfall areas of the East African High-lands and are characterized by low banana productivity. In these systems, the soil is tilled manually twicea year before bean planting with potentially damaging effects to the shallow banana root system. No-tillage with mulching (NT + M) may constitute an interesting alternative to conventional manual tillage(CMT) to avoid such root damage and improve banana productivity. The objectives of this study weretherefore (i) to assess tillage-induced damage to the banana rooting system and its subsequent recovery,and (ii) to evaluate the impact of three NT + M systems vs. CMT on banana root distribution and bananabunch weight. At two sites in the D.R. Congo, the cord root length density (RLD) and fresh weight (FW)were monitored monthly in the top 0.2 m of the soil over a 5 to 6-month period following manual tillage,and compared with NT + M plots. Immediately after tillage and on average over the two sites, cord RLDand FW in the top 0.1 m of the soil were reduced on average to 15% and 16%, respectively, of the levelsobserved under NT + M. At 0.3 m from the rhizome, cord roots needed 2–4 months to recover to a levelsimilar to the one observed prior to tillage. On average over the two sites, direct root damage by tillagecaused the loss of 47% and 63% of the RLD and FW observed in NT + M plots, respectively. The remainingrooting deficit (38% of RLD and 21% of FW) was hypothesized to originate from differences in root growthconditions unrelated to immediate mechanical root damage. There was no evidence that the mechanicaldamage of roots by tillage affected banana growth in the short term. The medium-term effect of CMT andNT + M treatments was evaluated at three sites (two in D.R. Congo and one in Rwanda) 30 months afterbanana planting. At two sites out of three, root density profiles indicated lower rooting densities in the top0.1 m of the soil in CMT plots compared with NT + M plots. Banana bunch weight was consistently lowerin CMT plots compared with NT + M plots. Compared with NT + M, CMT appears to affect banana rootingand bunch weight in the medium term under the pedo-climatic conditions of the East African Highlands.No-tillage with mulching may constitute an alternative to manual tillage to enhance the sustainabilityof these systems but its impact on the whole intercropping system’s productivity must be verified.